Delta Variant: The New Challenge of COVID-19 Pandemic, an Overview of Epidemiological, Clinical, and Immune Characteristics - Samieefar, Noosha; Rashedi, Ronak; Akhlaghdoust, Meisam; Mashhadi, Melika; Darzi, Pouya; Rezaei, Nima (Acta Biomedica Atenei Parmensis, 2022)
The SARS-CoV-2 genome has undergone several mutations since the beginning of the pandemic in December 2019. A number of these mutants were associated with higher transmissibility, higher mortality, or hospitalization rates, which were named the variants of concern.B.1.617.2 or the Delta variant has made a lot of concern as it has been responsible for the most recent COVID-19 outbreaks throughout the world. Higher transmissibility, a 60 percent increase in hospitalization rates compared to the wild type, higher viral loads, and reduced response to available vaccines are among the key factors why this variant has become a variant of concern. 148 countries are currently fighting with this variant, hoping to better understand the epidemiological, immunological, and clinical characteristics of this disease in order to find the best way to overcome these new outbreaks.Although reduced efficiency of vaccines on this variant and its higher pre-symptomatic transmissibility have made it complicated to control the disease, higher vaccination coverage and following sanitation rules can help control the outbreaks.